Educational ideas of Dean Francisco Benitez - Guanco, Nelia R. 1923- (1953)
The educational ideas of Dean Francisco Benitez, one of the foremost educators of the country, was presented in this paper.
Mimeographed.
Vita.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Education